55.1k views
2 votes
7(w+2)=-6(2w-1)+3wsolve for w.

User Joao Paulo
by
5.0k points

1 Answer

4 votes

To solve for w. The first step is to solve the common factor and then, solve similar terms to clear w.


\begin{gathered} 7(w+2)=-6(2w-1)+3w \\ 7w+14=-12w+6+3w \\ 7w+14=-9w+6 \\ 7w+9w=6-14 \\ 16w=-8 \\ w=-(8)/(16) \\ w=-(1)/(2) \end{gathered}

w is -1/2

User Michael Martinez
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.